Case of large spermatic cord lipoma misdiagnosed as inguinal hernia - Dandu, Shubha; Kamble, Pavan (International Surgery Journal, 2024)
Clinically, a pure spermatic cord lipoma has not been recognized as a disease entity but regarded as an incidental finding at the time of hernia repair because it presents as groin symptoms and clinical findings are indistinguishable from those of inguinal hernia. We report the successful treatment of case of huge pure spermatic cord lipoma originally misdiagnosed as inguinal hernia. A 65year male patient presented with progressive swelling, on and off pain in left groin in the last 2 years. On examination it was partially reducible and ultrasonographic scan was showing as inguinal hernia. We proceeded for an open hernia repair, unexpectedly it revealed a large fatty mass attached to spermatic cord and there is no connection to peritoneal cavity near deep ring. Then it is excised and Lichtenstein tension free hernioplasty was done to prevent future development of hernia. Histopathological examination of excised specimen confirmed it is a lipoma of cord.